2011
DOI: 10.1016/j.athoracsur.2011.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Use of Dexmedetomidine Is Associated With Decreased Incidence of Ventricular and Supraventricular Tachyarrhythmias After Congenital Cardiac Operations

Abstract: Background Postoperative tachyarrhythmias remain a common complication after congenital cardiac surgery. A recent case-series has shown that dexmedetomidine, an alpha-2 adrenoreceptor agonist can have a therapeutic role in supraventricular tachyarrhythmias for either cardioversion to sinus rhythm or heart rate control. The present study was performed to determine if routine perioperative use of dexmedetomidine can decrease the incidence of supraventricular and ventricular tachyarrhythmias. Methods Prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 21 publications
2
74
0
Order By: Relevance
“…It is utilized for postoperative sedation, as a component of total intravenous anesthesia regimens, for opioid-sparing in tonsillectomy, and also for premedication, procedural sedation, prevention of postoperative emergence agitation, and as a component of a balanced general anesthetic technique [33] . Among dexmedetomidine's desirable properties are its ability to maintain normal respiratory patterns, reduce the incidence of postcardiac surgical tachydysrhythmias [34] , and reduce doses of volatile anesthetic agents and opioids when utilized as a component of a balanced anesthetic technique [33] . Dexmedetomidine has a significant body of research and clinical publication in children; a recent PubMed search revealed over 500 publications in children 0-18 years, and 200 in children birth to 2 years of age.…”
Section: Dexmedetomidine As a Neuroprotectant In Anesthetic Neurotoximentioning
confidence: 99%
“…It is utilized for postoperative sedation, as a component of total intravenous anesthesia regimens, for opioid-sparing in tonsillectomy, and also for premedication, procedural sedation, prevention of postoperative emergence agitation, and as a component of a balanced general anesthetic technique [33] . Among dexmedetomidine's desirable properties are its ability to maintain normal respiratory patterns, reduce the incidence of postcardiac surgical tachydysrhythmias [34] , and reduce doses of volatile anesthetic agents and opioids when utilized as a component of a balanced anesthetic technique [33] . Dexmedetomidine has a significant body of research and clinical publication in children; a recent PubMed search revealed over 500 publications in children 0-18 years, and 200 in children birth to 2 years of age.…”
Section: Dexmedetomidine As a Neuroprotectant In Anesthetic Neurotoximentioning
confidence: 99%
“…Previous data support the potential use of dexmedetomidine as a therapeutic agent to treat perioperative arrhythmias in the pediatric population [ Table 1]. [15][16][17][18][19] Chrysostomou et al were the first to suggest the potential therapeutic role of dexmedetomidine in their retrospective review of the use of dexmedetomidine to treat 14 pediatric patients with tachyarrhythmias. [15] Dexmedetomidine was used as a primary drug in nine patients and as a rescue drug in five others when primary treatment had failed (amiodarone or amiodarone and hypothermia).…”
Section: Discussionmentioning
confidence: 97%
“…[17] Dexmedetomidine was started after the induction of anesthesia, continued intraoperatively and postoperatively for 38 ± 4 h at an average dose of 0.76 ± 0.04 µg/kg/h. Sustained postoperative arrhythmias occurred in 10 control patients compared with two patients who received dexmedetomidine (P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] No adverse effects on the pulmonary vasculature have been reported dexmedetomidine. [13,14] In a few anecdotal reports dexmedetomidine was successful in restoring SR in situations where routine antiarrhythmic agents had failed. [15][16][17] These reports clearly indicate that dexmedetomidine has antiarrhythmic actions.…”
Section: Dexmedetomidine In Pediatric Cardiac Anesthesiamentioning
confidence: 98%